2022
DOI: 10.1108/afr-01-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and its antecedents amongst the farmers: evidence from India

Abstract: PurposeThe article makes a modest attempt to explore the level of financial literacy (FL) amongst the farmers in India. An effort was also made to unearth the factors affecting such FL.Design/methodology/approachThe study used secondary data on 11,030 farmers across various regions of India from the Financial Inclusion Insight Survey, 2017. Standard and Poor Global FL questions were used to measure the level of FL amongst the respondents. In addition to the appropriate statistical tools and techniques, the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…, 2014). In tune with the findings of the study carried out by Maji and Laha (2023a), FI was also found to exacerbate a notable positive effect in augmenting the level of FL of Indian farmers. The average FL score of financially included Indian farmers was observed to be 33.85%, whereas the same was found to be 27.34% in respect of financially excluded farmers.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…, 2014). In tune with the findings of the study carried out by Maji and Laha (2023a), FI was also found to exacerbate a notable positive effect in augmenting the level of FL of Indian farmers. The average FL score of financially included Indian farmers was observed to be 33.85%, whereas the same was found to be 27.34% in respect of financially excluded farmers.…”
Section: Resultssupporting
confidence: 69%
“…The status of the farmer, i.e. owner or worker is a significant predictor of FL (Maji and Laha, 2023a). Farm owners were found to be more financially literate in India and Pakistan in tune with the findings of the study carried out by Maji and Laha (2023a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations